Features of the myocardial infarction course in convalescents of the new coronavirus infection COVID-19 - N. A. Muradyan; I. M. Kuzmina; T. R. Gvindzhiliya; V. M. Balanyan; K. A. Popugaev (Трансплантология (Москва), 2023)
Acute myocardial injury is one of the possible complications of the new coronavirus infection COVID-19 and can be diagnosed both in the acute phase of the infection, and also after stabilization or clinical improvement of the patient's condition. This review is devoted to the actual problem of the acute myocardial infarction development during the period of COVID-19 convalescence. The pathophysiological mechanisms of acute myocardial infarction during recovery from COVID-19 are diverse. The key role belongs to the state of hypercoagulation and the systemic inflammatory response, which can provoke destabilization and rupture of unstable atherosclerotic cardiac plaques. Type 2 acute myocardial infarction is most often diagnosed in COVID-19 convalescents against the background of intact coronary arteries. In this case, acute myocardial infarction develops due to an imbalance between increased myocardial oxygen demand (increased levels of cytokines in the blood, hypercatecholaminemia, hyperthermia and tachycardia) and a decrease in oxygen supply to cardiomyocytes due to hypoxemia and hypotension. Subclinical myocardial injury may be present despite normal coronary arteries on angiography and intact left ventricular ejection fraction. There is no clear relationship between the development of acute myocardial infarction during the period of COVID-19 convalescence and the severity of the infection, the time from the initial diagnosis, and the presence of traditional risk factors for cardiovascular diseases in the patient. Cardiac complaints in COVID-19 convalescents are often interpreted as a post-COVID syndrome, especially given the absence of a history of coronary heart disease in many patients, which can lead to late diagnosis. Further study of the features of acute myocardial infarction during the period of COVID-19 convalescence is needed.